Elastic surface plasmon polariton scattering: near- and far-field interactions - Segovia Olvera, Paulina; Coello, Víctor (2012)
Using a vectorial dipolar model for multiple surface plasmon-polariton (SPP) scattering, we investigate propagation and elastic (in-plane) scattering of SPP's excited in the wavelength range of 543 633 nm at random nanostructured gold surfaces. The model makes use of a composed analytic Green dyadic which takes into account near- and far-¯eld regions, with the latter being approximated by the part describing the scattering via excitation of SPP. Simultaneous SPP excitation and in-plane propagation inside square-random arrays of nanoparticles were observed with di®erent density of particles, demonstrating the feasibility of the suggested approach. The composed Green dyadic represents an improvement of previous SPP simulations for random nanoparticles arrays since it permits SPP scattering simulations for more realistic systems with relatively large number of close, or even in contact, nanoparticles. Our results suggest that this numerical approach is quite promising for the quantitative description of lightSPP coupling and associated processes such as weak and strong SPP localization.